(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the present research work was to enhance the rate of in vitro drug release profiles of poorly soluble Rilpivirine Hydrocloride (RH) by Spray drying technique. Rilpivirine is a non-nucleoside reverse transcriptase inhibitor of human immunodeficiency virus type-1 (HIV-1). Method: RH is belongs to BCS class-II. It is insoluble in water and practically insoluble across the pH range of 1 â€“ 7.5. One of the major concerns with the formulation of RH is its poor solubility, which results into poor bioavailability after oral administration. Spray drying technique has been proven to be an efficient technique for conversion of poorly soluble crystalline form into highly soluble amorphous form and make it useful for formulating lab scale batches to commercial batches. Hence, Spray drying technique was chosen for reducing the % of crystallinity / or converting crystalline form into highly soluble amorphous form by spray drying technique. The organic dispersion comprising RH, hydrophilic carriers like Soluplus / Kollidon VA64 / Kolliphor SLS / Kolliphor P407 / Kollidon 30 at different ratios along with finer grade of microcrystalline cellulose (Avicel PH 105) was subjected to spray drying using Buchi spray dryer. Results & Discussion: The dissolution profiles of formulated product (RT2 & RT3) in FDA recommended dissolution media was compared against the dissolution profiles of corresponding innovator product. The rate of in vitro drug release was at faster and complete from test product as compared to Innovator product profiles i.e., EUDRANTâ„¢ 25 mg tablets. From the characterization of spray dried powder RSD8 by DSC and XRD concluded that % crystallinity of RH was reduced significantly. Conclusion: The obtained results suggested that Spray drying technique might be an efficacious approach in enhancing the therapeutic potential of Rilpivirine Hydrochloride.